O Reino de Deus: Realidade atual e escatológica - Xavier, Érico Tadeu (Kairós: Revista Acadêmica da Prainha, 2021)
As a central part of Christ's teachings, the Kingdom of God has great relevance for the Christian Church. In this sense, the purpose of this study is to analyze the meaning of the Kingdom of God for the Christian Church and its importance in the message of salvation. The Church must understand the meaning of the Kingdom of God and its implication in the context of the preaching of the Gospel, so that it can experience and spread the Gospel message in the present moment, while awaiting the concretization of the Gospel in the soon return of Christ.